Ca2+ channelopathies - Friel, David (Henry Stewart Talks, 2012)
Gene mutations viewed in the context of the central dogma of molecular biology, Relationship between genotype and phenotype and the impact of mutations, Classification of ion channels and channelopathies, Structure function relations for voltage-gated Ca2+ channels, P/Q type Ca2+ channelopathies, Ca2+ channel mutations and sources of cell- and circuit-level phenotypic diversity, Distinction between mutations and polymorphisms
Archived at 2022/01/31